A holistic exploration of porous asphalt mixtures: From durability and permeability to low-temperature and functional properties - Yue Zhou; Zhiqiang Cheng; Xiaoguang Zheng; Tao Wang; Xiaoliang Wu; Xiaoxiao Yu; Shengjia Xie (Heliyon)
This article provides a comprehensive review of the research progress on porous asphalt mixtures, focusing on their durability, permeability, low-temperature performance, and functionality. The study examines factors influencing the anti-raveling performance of porous asphalt, including modified asphalt binders, fibers, aggregates, traffic loads, and environmental conditions. It also discusses the impact of porosity, pore structure, and temperature variations on the low-temperature cracking resistance of porous asphalt. Furthermore, the article explores the permeability of porous asphalt mixtures, emphasizing the influence of pore characteristics, water flow directions, clogging processes, and pavement designs. The sound absorption and skid resistance properties of porous asphalt are also analyzed, highlighting the importance of porosity, texture depth, material properties, and water film thickness. The study concludes by proposing improvement measures and optimization suggestions for porous asphalt mixtures, providing valuable references for future research and applications. Finally, several future research topics for porous asphalt mixture are proposed. Further studies on porous asphalt pavement involves seeking performance balance, ensuring improvement without detriment. Researching factor interactions, building a model, exploring industrial waste use to cut costs, reduce pollution and promote its environmental application for diverse traffic and environment needs.